Novice head teachers' isolation and loneliness experiences: A mixed-methods study. (January 2017) - Tahir, Lokman; Thakib, Mohd Taufiq Mohd; Hamzah, Mohd Hilmi; Said, Mohd Nihra Haruzuan Mohd; Musah, Mohammed Borhandden
Most studies in headship focus on the elements of training and head teachers' capabilities in leading schools. The concept of isolation experienced by head teachers during the early years of their headship is, however, overlooked. This article attempts to explore the neglected aspect of headships' experiences with isolation that later contributes to the betterment of the headship appointment. This mixed-methods study explores the experience of head teachers' isolation in the early phase of their leadership years, and presents findings on the strategies used to overcome the isolation. Using an open-ended questionnaire, a total of 170 novice head teachers from Malaysian primary and secondary schools were asked to give their responses on experiences of isolation. Furthermore, 10 novice head teachers, who experienced isolation in the early phase of their leadership years, were interviewed. Findings revealed that the level of isolation among the head teachers was fairly low, and they perceived their isolation experience as temporary.